The Idea of Event in Althusser and Badiou Philosophy’s: a Way to Rethink the Political Subjectivities - Ignacio Gordillo (Oxímora. Revista Internacional de Ética y Política, 2019)
This paper examines the attempts for rethinking philosophically the political in the works of Louis Althusser and of Alain Badiou in the period in which they face theoretically to the so-called “crisis of the Marxism”. In Althusser's case, former representative of Marxism structuralism, this project is nourished by the philosophers belonging to a materialistic tradition that also recognizes the contingency, and he is interested particularly for Machiavelli, due to his particular approach to the political question. Badiou, former pupil of Althusser, think this question with the category of the event, linked to an exception characterized ontologically in L'Être et l'événement. Finally, this article explores in what sense for this authors the occurrence of an event can be linked to the emergence of a subjectivity that exceeds the structural frame.